Intelligent photovoltaic panels based on solar tracking. Issue 1 (2nd January 2020) - Kanotra, Mehul; Gupta, Yash; Massey, Pranika; Leekha, Alka
Abstract: The transformation of solar energy into electricity using photovoltaic cells has many economic and environmental benefits. As this technology reduces dependence on non-renewable energy sources, many developed and developing countries near the equator are increasingly willing to adopt such energy generation techniques. Its tilt angle with the horizontal plane and its orientation determines the photovoltaic panel (PV) yield. Thus the solar energy obtained from traditional photovoltaic panels can be maximized by replacing them with Intelligent photovoltaic panels. The Intelligent Photovoltaic panels adjust its orientation as well as tilt angle automatically with changing sun direction to receive maximum possible solar energy on its surface. A handful of studies on the orientation of tilt angle and its optimization have been conducted to improve the yield of photovoltaic panels; however, no solution has been proposed to estimate the optimum value of the parameters based on real-time monitoring.